Poligami Perspektif Hermeneutika Fazlur Rahman - Burhanuddin Burhanuddin (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2019)
Polygamy is one area that is still warm to be discussed. Sensitivity is very flexible when faced with psychological and emotional factors of women. In this part, there was a polemic and many rejected it. And not a few women also agree to polygamy. There is also in the realm of economics, power and order of disharmony become part of the reasons for men to carry it out heavily. Because this part demands justice. It is at this point that the focus of study and academic anxiety is viewed from the aspect of hermeneutic science. The term hermeneutics is often used as a method of interpretation in the Qur'an because hermeneutics is the reading of texts from the historical side and the relativity of life. Even more hermeneutics is interpreted as an understanding of the contextual to look for the meaning behind the text of the verse. Related to the interpretation of the verse polygamy, among some classical commentators say that, the context of polygamy in the Qur'an is still permissible, because the interpretation uses the understanding of the text in the sense that it is in accordance with what is mentioned in the Qur'an without considering the implications will happen in life. However, there are contemporary scholars who offer to be tested and reviewed their sociological value so that social disintegration does not occur. This is an interesting issue in Fazlurrahman's thought to try to reinterpret themes related to polygamy using the hermeneutic approach. Thus, this paper highlights Fazlur Rahman's hermeneutic approach that has been applied in interpreting verses of polygamy in the Qur'an.